Attitude of undergraduate medical students towards euthanasia and physician-assisted suicide: a cross-sectional study - Mahnoor; Shahid, Aiza Noor; Shafiq, Haleema; Aslam, Noman; Ayub, Ayesha (Journal of the Pakistan Medical Association, 2024)
Euthanasia is categorically prohibited in Pakistan by Islamic law, but a clash of opinions among doctors and human rights advocates still prevails. As a result, medical students are becoming concerned about its practice and this problem needs to be addressed. A cross-sectional study was conducted at Faisalabad Medical University (FMU), Pakistan, from April 2023 to May 2023, using random sampling and statistical programme SPSS version 25, to assess the attitudes of medical students regarding euthanasia and physician-assisted suicide (PAS). Despite the conditions and scenarios presented to the students, most of them expressed opposition to euthanasia and physician-assisted suicide because of their religious beliefs and optimistic approach to life. Most of them favoured palliative care and passive euthanasia. ---Continue